The Impact of Hedonic Shopping Motivation towards Impulse Buying Behavior moderated by money availability, time availability, and task definition: A case of ZARA in Indonesia - Chynthia Fang (iBuss Management, 2020)
Past studies found that impulse buying is affected by hedonic motivation. Moreover, hedonic people are likely to experience impulse buying behavior during their shopping activity since it involves pleasure seeking. Hedonic motivation can be enhanced through fashion products, such as ZARA, which is the focus of the research. Besides hedonic motivation, several studies have taken into account the moderating effect of situational characteristics (money availability, time availability, and task definition), which often found to moderate the relationship between hedonic motivation and impulse buying. Thus, in this research, the researcher study the effect of hedonic shopping motivation towards impulse buying behavior, moderated by money availability, time availability, and task definition in the case of ZARA in Indonesia. The questionnaire was filled by 100 eligible respondents using simple random sampling, and the data was analyzed using moderated regression analysis. The study found that hedonic motivation affects impulse buying, while money availability, time availability, and task definition are found to moderate the relationship between hedonic motivation and impulse buying. Keywords: Hedonic Shopping Motivation, Impulse Buying Behavior, Money Availability, Time Availability, Task Definition